Jebakan Toxic Positivity Berlabel Ibadah: Dekonstruksi Makna Amanah dalam Manajemen Kesejahteraan Mental Guru Madrasah - Samsul Hadi; Tarekah Hasanah; Muhammad Akmansyah (STKIP PGRI Bandar Lampung, 2026)
The mental health of madrasah teachers is a crucial issue often overlooked behind narratives of piety and devotion. This study aims to uncover the phenomenon of toxic positivity labeled as worship and deconstruct the meaning of